TYPES AND CRIMINAL LEGAL ASPECTS OF THE THEFT OF PROPERTY USING BANK PLASTIC CARDS - Kholikov Farhod Uktamovich (Modern American Journals, 2026)
This article discusses the practice of stealing bank plastic cards and the problems of their qualification, as well as measures to prevent this type of crime. Also, proposals for improving the national legislation of the Republic of Uzbekistan were developed.
Keywords: Bank plastic cards, Skimming, Phishing, Vishing, IM-frod